2019
DOI: 10.3384/diss.diva-162113
|View full text |Cite
|
Sign up to set email alerts
|

Keeping track of time : Daily time management, participation, and time-related interventions for children, adolescents, and young adults with neurodevelopmental disorders

Abstract: The overall aim of this thesis was to investigate daily time management (DTM) and time-related interventions aiming to enhance participation in everyday activities among school-age children and young adults with neurodevelopmental disorders. I was delighted to have the opportunity to start research in this area! This thesis can contribute to knowledge about daily time management for people with neurodevelopmental disorders. I also hope that the thesis can arouse interest and inspiration in providing tools for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(189 reference statements)
0
1
0
Order By: Relevance
“…Many parents use the Internet as support in their parenthood, and for many, it is the firsthand choice to find information about pregnancy and parenthood, including infant feeding [ 19 - 21 ]. Despite this, studies have shown that among health care personnel there exists a negative attitude toward social media and a concern about patients seeking information online [ 22 , 23 ]. With the knowledge of what is actually discussed about introducing formula feeding on parenting Web forums, health care personnel can have a better understanding of the situation, and thus will be able to better adjust the breastfeeding support with the family’s needs.…”
Section: Introductionmentioning
confidence: 99%
“…Many parents use the Internet as support in their parenthood, and for many, it is the firsthand choice to find information about pregnancy and parenthood, including infant feeding [ 19 - 21 ]. Despite this, studies have shown that among health care personnel there exists a negative attitude toward social media and a concern about patients seeking information online [ 22 , 23 ]. With the knowledge of what is actually discussed about introducing formula feeding on parenting Web forums, health care personnel can have a better understanding of the situation, and thus will be able to better adjust the breastfeeding support with the family’s needs.…”
Section: Introductionmentioning
confidence: 99%